Новый род пчелиных трибы Anthidiini (Hymenoptera, Apoidea, Megachilidae) с Дальнего Востока - Романькова, Т.Г. (Вестник зоологии, 1988)
Lasanthidium Romanjkova, gen. n. (type-species: Stelis malaisei Popov, 1941) is distinct by 3-segmented maxillar palpae, dense, deep body punctuation, female with abdominal brush, nest in the timber using timber resin.